Analisis Kualitas Pelayanan Teller Pada Bank Woori Saudara KCP Ciamis - Hastuti, Sri; Kurniawati, Yuyun; Munggaran, Rangga (Jurnal Ekonomi Bisnis dan Manajemen, 2025)
This study aims to analyze the quality of teller service at Bank Woori Saudara Ciamis Branch based on the five SERVQUAL dimensions, which include physical evidence (tangibles), reliability, responsiveness, assurance, and empathy. The research method used is descriptive quantitative with a non-probability sampling technique using Slovin's formula. The research sample consists of 100 respondents from a total population of 4,994 customers. Data was collected thru questionnaires and analyzed using a descriptive approach by calculating the average score for each dimension. The research results show that the overall average score is 3.22, which falls into the fairly high category. This indicates that the teller service at Bank Woori Saudara Ciamis Branch is generally good, although there are still some aspects that need improvement, such as queue order and service speed. In conclusion, the quality of teller service has reflected professionalism and a friendly attitude in serving customers, but improved consistency and competence are still needed to achieve excellent service standards.